SISTEM INFORMASI KARYAWAN PADA PT.LESTARINDO UTAMA KARYA (LUK): Employee,Information System,PHP,Website - afrizal, afrizal; LOUIS, AHMAD; IMAM, CHOIRUN (FORTECH (Journal of Information Technology), 2025)
PT.Lestarindo Utama Karya (LUK) is a company engaged in the industrial processing of logs into plywood or also called plywood. Every day the factory processes logs into plywood of various sizes and materials.PT. Lestarindo Utama Karya (LUK) is a company that employs quite a number of employees.However,in processing data related to employee records and calculating employee salaries, Microsoft Excel is still not optimal. The use of Microsoft Excel that is less than optimnal allows for many errors to occur which result in many obstacles such as many errors in data collection, as wel as delays in preparing reports. With this problem analysis,researchers provide solutions related to the problems faced by these agencies by developing a staffing information system, where the system can make it easier for employees to access all information data about staffing and make it easier to make reports. The data to be inputted are user data,attendance data,position data,employee data and salary data.With output in the form of employee reports, position reports, attendance reports and salary repots. With the creation of a web-based staffing information system,it is hoped that it will make it easier for the personnel department to carry out its duties as a recruiter.